PERBANDINGAN PENGATURAN PENGAMANAN PERDAGANGAN (SAFEGUARD) DI INDONESIA DAN VIETNAM: Comparison of Trade Safeguard Regulations in Indonesia and Vietnam - Sutan Raikhan Hanifaputra Ardiansyah; Rosdiana Saleh (Reformasi Hukum Trisakti, 2026)
Import surges in international trade have the potential to cause serious injury to domestic industries, thereby requiring states to adopt lawful legal instruments to provide protection. One such instrument is the trade safeguard measure, which is regulated under the framework of the General Agreement on Tariffs and Trade (GATT) 1994 and the Agreement on Safeguards. This study aims to analyze the similarities and differences in the regulation of import safeguard mechanisms in Indonesia and Vietnam. The research employs a normative legal method with a comparative law approach through the analysis of statutory regulations and legal literature. The findings indicate that both countries adopt safeguard provisions based on international trade law. however, they differ in legislative structure, institutional design, and procedural mechanisms of implementation. In conclusion, these regulatory differences reflect variations in policy orientation and levels of legal certainty in each country, despite operating within the same international trade law framework.